Fungal graviresponses: Physiological and molecular insights from tissue reorientation in the gravity vector - Alexander Baena; D. Marshall Porterfield (Mycology)
Graviresponses, the growth responses of organisms to gravitational alterations, are pivotal yet understudied phenomena in fungi compared to plants and animals. Fungi perceive gravity through proposed statoliths, including nuclei connected to actin filaments, octahedral protein crystals, and floating lipid globules. These mechanisms generate sufficient potential energy to overcome thermal noise and establish detectable gradients within cells. Signal transduction involves ion fluxes, reactive oxygen species, and cytoskeletal components, transducing physical signals into polarised cell wall loosening. In mushroom-forming fungi, gravitropic responses manifest primarily through differential hyphal elongation in the stipe, while gravimorphogenetic responses cause broader developmental and morphological changes. Though basic fruiting body formation can occur in microgravity, proper spore dispersal requires gravity sensing which triggers molecular mechanisms involving precise regulation of cell wall modification, vesicle trafficking, and complex signalling cascades, particularly in specialised tissues of the fruiting body. Curvature compensation mechanisms ensure optimal vertical alignment of spore-bearing tissues through feedback systems. Studies of model organisms like Coprinopsis cinerea, Flammulina velutipes, and Phycomyces blakesleeanus have revealed species-specific gravisensing mechanisms that reflect diverse ecological strategies for spore dispersal. Despite advances in understanding these mechanisms, key questions remain about morphogenetic regulation and signal transduction. This review examines classical and modern findings while highlighting opportunities for investigation using contemporary molecular approaches.